COMPLEMENTARITY IN THE DEVELOPMENT OF RURAL TOURISM WITH THE DEVELOPMENT OF THERMAL BATHS, SPA AND WELNESS TOURISM - Vuković, Predrag; Čavlin, Gordana; Čavlin, Miroslav (Economics of Agriculture, 2015)
Serbia has a long tradition in thermal baths tourism development. In the second half of the twentieth century, this branch of tourism attracted a significant segment of tourist demand, both domestic and foreign. However, due to difficult business conditions in the nineties, its infrastructure became outdated. This resulted in negative trends in tourism development and a negative image appeared in the tourism market. On the other hand, rural tourism is a relatively new form of tourism. In Serbia, it started developing from the 1970ies. A significant interim in this form of tourism was also noticed during the nineties. Today, these two forms of tourism are emphasized as the development chance of Serbian tourism and economy in diverse development-strategic documents by the Government and the departmental ministry. The conceptual approach to these forms of tourism is used in this work, in order to scope the possibilities of their complementary development. What is primarily borne in mind is the resource basis that Serbia possesses for their development, but also the newer tendencies and trends on the tourism market. Expectations are that a synergic cooperation of these forms of tourism would ensure better results, and Serbia would position itself higher on the international tourism market.